Mechanical characterization of a shape morphing smart composite with embedded shape memory alloys in a shape memory polymer matrix. (August 2016) - Lelieveld, Charlotte; Jansen, Kaspar; Teuffel, Patrick
This article presents a smart composite that shows a reversible bending deformation from an initial flat configuration into a 90° angle controlled by local thermal activation. The novelty lies within the structural fixation of the deformation at room temperature without continuous energy input. The new structural architecture of antagonistic performing shape memory alloy actuators embedded in a shape memory polymer matrix is presented. The shape memory polymer is locally heated from the rigid glassy state to the easily deformable rubbery state by integrated heating wires. By subsequent activation of the different shape memory alloy actuators by resistive heating, the reversible performance can be realized. By deactivation of the heating wires in the shape memory polymer, the shape memory polymer fixates the deformation in its rigid condition. The actuation characteristics of the smart composite are investigated by thermo-mechanical experiments. The performance of the smart composite was investigated by thermo-mechanical experimentation of the individual components. The results show that a 90° bending deformation is feasible with the current material dimensions, but repeated deformation is restricted due to fatigue of the alloy. By superposition of the bending forces of the individual components, it is possible to estimate the bending angle of the composite material.